Portrait Of A Scotsman : A League of Extraordinary Women #3 - Dunmore, Evie (New York : Jove, 2021)
"Going toe-to-toe with a brooding Scotsman is rather bold for a respectable suffragist, but when he happens to be one's unexpected husband, what else is an unwilling bride to do? London banking heiress Hattie Greenfield wanted just three things in life: 1. Acclaim as an artist 2. A noble cause 3. Marriage to a young lord who puts the gentle in gentleman Why then does this Oxford scholar find herself at the altar with the darkly attractive financier Lucian Blackstone, whose murky past and ruthless business practices strike fear in the hearts of Britain's peerage? Trust Hattie to take an invigorating little adventure too far. Now she's stuck with a churlish Scot who just might be the end of her ambitions. . . . When the daughter of his business rival all but falls into his lap, Lucian sees opportunity. As a self-made man, he has vast wealth but holds little power, and Hattie could be the key to finally setting long-harbored political plans in motion. Driven by an old revenge, he has no room for his new wife's apprehensions or romantic notions, bewitching as he finds her. But a sudden journey to Scotland paints everything in a different light. Hattie slowly sees the real Lucian and realizes she could win everything-as long as she is prepared to lose her heart"--.
"A Jove book"--Title page verso.
Keywords: Romance fiction